Gibrat's Law and Market Selection in the Radio, TV & Telecommunications Equipment Industry - Francesca Lotti; Enrico Santarelli; Marco Vivarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
According to Gibrat's Law of Proportionate Effect, the growth rate of a given firm is independent of its size at the beginning of the period examined. In contrast to the previous literature on the subject, this paper seeks to test the Law by taking account of both the entry process and the role of survival/failure in reshaping a given population of firms over time. It does so by focusing on the entire population of firms (including newborn ones) in the Italian Radio, TV & Telecommunications equipment industry and tracking them over seven years. Consistently with the previous literature, it finds that - in general - Gibrat's Law is to be rejected, since smaller firms tend to grow faster than their larger counterparts. However, the paper's main finding is that this rejection of Gibrat's Law may be due to market dynamics and selection. In other words, it is due to the entry process and the presence of transient smaller firms. Indeed, whilst it is found that Gibrat's Law has to be rejected over a seven-year period during which both incumbent and newborn firms are considered, for both sub-populations of surviving firms a convergence towards Gibrat-like behavior over time can be detected. Thus, market selection "cleans" the original population of firms and the resulting industrial "core" (mature, larger, well-established and most efficient firms) does not seem to depart from a Gibrat-like pattern of growth.
Keywords: 330